Translation as the mutual reflection of neighbouring nations: About the cultural activity of Kornél Szenteleky - Virág, Zoltán (Slavia Centralis, 2020)
In the context of Kornél Szenteleky’s volumes of short stories, novels and essays, this essay examines the types of disposition, life experience, typical topographies and genres of the author’s epic works. The roles, stock of phrases and experiences of deprivation present in the world of Szenteleky’s short stories, novels and essays relate his prose to several authors of a significant trend in Croatian, Serbian and Slovenian literature. The essay observes the existential spaces and boundaries of Szenteleky’s oeuvre, viewing it as going along the trails of existential experience of multiethnicity, minority identity, peripheral existence, cultural crossroads and traumas.
Keywords: Kornél Szenteleky; cultural activism; regional identity; multiethnicity; experience of deprivation; mutual reflexivity